2004
DOI: 10.1038/ncb1188
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide induces coupling of mitochondrial signalling with the endoplasmic reticulum stress response

Abstract: Nitric oxide (NO) is a pleiotropic signalling molecule that binds to cytochrome c oxidase (complex IV) reversibly and in competition with oxygen. This action of NO has both physiological and pathophysiological consequences. Here we report that endogenously generated NO, which disrupts the respiratory chain, may cause changes in mitochondrial calcium flux. This induces cleavage of the endoplasmic reticulum (ER) stress-regulated transcription factor p90 ATF6 into an active p50 form. Cleavage depends on a calcium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
136
1
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 164 publications
(141 citation statements)
references
References 30 publications
3
136
1
1
Order By: Relevance
“…Studies using genetically targeted Ca 2+ -selective probes (such as the bioluminescent protein aequorin) or fluorescent dyes (such as rhod-2) have provided a direct and unambiguous readout of mitochondrial Ca 2+ changes in living cells following receptor stimulation. Recently we found that in NOgenerating cells there is a disruption in the respiratory chain and a decreased respiration rate that is accompanied by a mitochondrial Ca 2+ flux [11]. These findings are in agreement with previous reports showing that exogenous NO [12] and peroxynitrite [13,14] can result in the release of Ca 2+ from mitochondria.…”
Section: No and The Endoplasmic Reticulum Stress Responsesupporting
confidence: 93%
See 2 more Smart Citations
“…Studies using genetically targeted Ca 2+ -selective probes (such as the bioluminescent protein aequorin) or fluorescent dyes (such as rhod-2) have provided a direct and unambiguous readout of mitochondrial Ca 2+ changes in living cells following receptor stimulation. Recently we found that in NOgenerating cells there is a disruption in the respiratory chain and a decreased respiration rate that is accompanied by a mitochondrial Ca 2+ flux [11]. These findings are in agreement with previous reports showing that exogenous NO [12] and peroxynitrite [13,14] can result in the release of Ca 2+ from mitochondria.…”
Section: No and The Endoplasmic Reticulum Stress Responsesupporting
confidence: 93%
“…The NO-mediated ER stress response is diminished in rho 0 cells that are devoid of mitochondrial DNA. Therefore, our work has shown that NO signals, via mitochondrial respiration, to the ER stress response with consequences for cell survival or death [11].…”
Section: No and The Endoplasmic Reticulum Stress Responsementioning
confidence: 90%
See 1 more Smart Citation
“…Interestingly, recent studies have revealed a role for S-nitrosylation in the regulation of vesicular trafficking in endothelial and epithelial cells (4, 7), platelets (5), and neurons (6). In addition, nitric oxide has been identified as a proximal mediator of ER stress responses, although the role of S-nitrosylation was not evaluated (27).…”
Section: Evaluation Of S-nitrosylation In Hasmc By Immunogold Electronmentioning
confidence: 99%
“…While nitric oxide stimulates cellular damage, it also activates a number of signaling pathways that limit additional cellular damage and repair existing damage. In pancreatic ␤-cells, the protective responses activated by nitric oxide include (i) JNK-dependent induction of GADD45␣ (growth arrest and DNA damage-inducible protein 45␣) and DNA repair, (ii) activation of AMP-activated protein kinase (AMPK), resulting in enhanced metabolic recovery, and (iii) activation of the unfolded-protein response (UPR) (25,34,38,54,57,61).AMPK is a conserved heterotrimeric (␣, ␤, and ␥ subunits) serine/threonine kinase involved in sensing and responding to the energetic demand within eukaryotic cells (15). AMPK is activated by phosphorylation at threonine 172 in the catalytic ␣ subunit (19) in a constitutive fashion by the upstream kinase LKB1; however, this phosphorylation is rapidly removed by a phosphatase to maintain low basal activity (18,43).…”
mentioning
confidence: 99%